2023
DOI: 10.3389/fped.2022.1059728
|View full text |Cite
|
Sign up to set email alerts
|

Lactate dehydrogenase and the severity of adenoviral pneumonia in children: A meta-analysis

Abstract: BackgroundChildren with severe adenoviral pneumonia (ADVP) have poor prognosis and high risk of mortality. We performed a meta-analysis to evaluate the association between pretreatment lactate dehydrogenase (LDH) and severity, postinfectious bronchiolitis obliterans (PIBO), and mortality in children with ADVP.MethodsRelevant observational studies were identified by search of PubMed, Embase, Web of Science, Wanfang, and CNKI databases from inception to August 3, 2022. A random effect model was used to pool the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…LDH is a cytoplasmic enzyme that is present in most cells. LDH activity changes when the cell membrane is damaged; therefore, the amount of LDH released can reflect the degree of cell damage [ 37 , 38 ]. Cytotoxicity assay results indicated that lnc001776 overexpression significantly increased LDH levels ( Figure 3 E).…”
Section: Resultsmentioning
confidence: 99%
“…LDH is a cytoplasmic enzyme that is present in most cells. LDH activity changes when the cell membrane is damaged; therefore, the amount of LDH released can reflect the degree of cell damage [ 37 , 38 ]. Cytotoxicity assay results indicated that lnc001776 overexpression significantly increased LDH levels ( Figure 3 E).…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have found that the LDH level is an independent risk factor for the development of BO after MP pneumonia ( 17 19 ), but there are no reports in ADV-PIBO. Although the study of Zou et al also suggests that pretreatment LDH was significantly higher in children with severe ADV pneumonia who developed PIBO than in those who did not, it was not an independent risk factor ( 20 ). The increase in LDH levels suggested severe lung injury, which may induce excessive abnormal repair, may play a role in the pathogenesis of BO.…”
Section: Discussionmentioning
confidence: 99%
“…LDH is present in the cytoplasm of all tissues and cells. In damaged tissues or cells, LDH levels increase, which is a crucial indicator of the inflammatory response [36,37]. Hong et al [38] revealed that lncRNA NONHSAT217600.1 knockdown attenuated neodymium oxide (Nd 2 O 3 )-induced LDH release and reduced inflammatory damage in 16HBE human bronchial epithelial cells.…”
Section: Discussionmentioning
confidence: 99%